2008
DOI: 10.1016/j.bandc.2008.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment effects on eye movement control

Abstract: The increasing use of eye movement paradigms to assess the functional integrity of brain systems involved in sensorimotor and cognitive processing in clinical disorders requires greater attention to effects of pharmacological treatments on these systems. This is needed to better differentiate disease and medication effects in clinical samples, to learn about neurochemical systems relevant for identified disturbances, and to facilitate identification of oculomotor biomarkers of pharmacological effects. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(154 citation statements)
references
References 186 publications
1
142
0
4
Order By: Relevance
“…Studies correlating eye movement properties, symptomatology and medication dose have shown discordant results 6,[11][12][13]23,28 . Controlled studies comparing the effects of risperidone and olanzapine have found a decrease in the mean length of the saccadic movements in schizophrenia patients compared to controls but no difference was found among patients due to the medication type 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies correlating eye movement properties, symptomatology and medication dose have shown discordant results 6,[11][12][13]23,28 . Controlled studies comparing the effects of risperidone and olanzapine have found a decrease in the mean length of the saccadic movements in schizophrenia patients compared to controls but no difference was found among patients due to the medication type 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of oculomotor tasks offers an advantageous tool to evaluate pharmacological effects on cognitive and motor functions (Reilly et al, 2008). The smooth pursuit eye movement (SPEM) task requires a mechanism to track a moving object in extra-personal space without head movement and draws upon attention, motion processing and temporo-spatial prediction (Barnes, 2008).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Intravenous administration of fentanyl 100 µg adversely affected oculomotor function, but the effect does not last more than 15 to 30 min [72]. Oculomotor function is not known to be affected by serotonin-specific reuptake inhibitor (SSRI) antidepressants, indicating that these medications should not produce a false positive reading of abnormal function [73]. The lack of oculomotor effect from SSRI antidepressants is important because these medications are first-line pharmacotherapy agents in PTSD and major depression.…”
Section: Diagnosis Of Tbi In Setting Of Ptsd or Other Psychiatric Comentioning
confidence: 99%